The pattern of acute respiratory infections treatment in children of 0 – 59 month’s old in Puskesmas I Purwareja, Banjarnegara year of 2004 - Wahyono, Djoko; Hapsari, Indri; Budi Astuti, Ika Wahyu (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2008)
The purpose of this research was to describe the pattern of acute of respiratory tract infections in children of 0-59 month’s old in Puskesmas I Purwareja Klampok, Banjarnegara. The data was taken by retrospective method from medical record. The data collected was analysed by nonanalytic descriptive statistic method, and then compared them to standard of therapy provided by Indonesian Health Departement. The result showed that all of 120 patients were pneumonia acute respiratory tract infections, which were 55.8% boys and 44.2% girls. The antimicrobials used were Cotrimoxazol (86.7%) and amoxicillin (13.3%). The major product used in that puskesmas was syrup (91.7%), and tablet that delivered in the form of powder was 8.3%. The treatment using these antimicrobial at Puskesmas I Purwareja, Klampok, Banjarnegara was in accordance to standard of therapy provided by Indonesian Health Departement. Key words: pneumonia acute respiratory tract infection, 0-59 months old children, antimicrobial, puskesmas I Purwareja Klampok Banjarnegara